Pemodelan Alat Peraga Praktikum Sistem Pembangkit Listrik Tenaga Air Pico Hydro dengan Turbin Propeller Type Open Flume Tc 60 - Nurjan Didik Purwanto; Sugiarto Sugiarto (Jurnal Ilmiah Teknik Pertanian - TekTan, 2020)
Modeling of Practical Teaching System for Pico Hydro Hydroelectric Power Plant with Open Flume TC 60 "Turbine Propeller Type is a practical teaching aid made in order to increase diversity and practicum facilities for students of Agricultural Mechanization study programs in the Energy and Electricity Agriculture course. At the same time this Practical Modeling introducing various types of renewable energy (reneable energy) to the academics at the Lampung State Polytechnic, besides that, the making of this tool also has the following objectives:-   Make modeling of laboratory scale pico hydro power generation systems with Open Flume TC 60 Type Propeller Turbines.-   Here the tool that students are expected to be able to design  a pico hydro power plant.-   Increase the diversity of practicum equipment in the Agriculture Mechanization laboratory.-   Streamlining the process of teaching and learning activities in the laboratory.Thus this tool is expected to contribute to the world of education, especially for students of the Lampung State Polytechnic Mechanization of Agriculture study program. Keywords: pico hydro hydroelectric power, and reneable energy